Falls in unilateral lower limb amputees living in the community. A Portuguese study. - Engenheiro, Gonçalo (2020)
Introduction: Lower limb amputees present a high risk of falling. This study aims to characterise fall history in unilateral lower limb amputees that are autonomous in the community, identifying differences between transfemoral and transtibial amputees and assessing fear of falling between fallers and non-fallers.Material and Methods: Descriptive, cross-sectional study of consecutive community-dwelling unilateral lower limb adult amputees of any aetiology, attending outpatient consultation in a Portuguese Physical and Rehabilitation Medicine central and university hospital department. Inclusion criteria: a prior 12 week individualised rehabilitation program for prosthesis training; regular prosthesis use for more than one year with autonomous gait; and a Functional Independence Measure® score equal to or greater than 100. Injury severity was classified according to the National Database of Nursing Quality Indicators® injury falls measure. In order to assess walking performance over short distances and fear of falling we used the 10-meter walk test and the Falls Efficacy Scale, respectively.Results: In a sample of 52 lower limb amputees, mainly men (80.8%) and of traumatic aetiology (63.5%), with a mean age of 57.21 ± 11.55 years, 36.5% reported at least one fall in the previous 12 months, all classified as minor injuries. Transfemoral amputees (n = 23) presented a higher number of falls (2.22 ± 3.23, p = 0.025) and lower gait velocity (0.77 ± 0.26 m per second, p < 0.001). Regarding fear of falling, we found no significant differences between fallers and non-fallers.Discussion: The prevalence of falls was low and of minor severity. Transfemoral amputees fell more often and were slower. There were no reported differences in fear of falling between groups.Conclusion: This paper contributes information about Portuguese lower limb amputees, whose studies are scarce and are rarely dedicated to falling.